Influence Non Performing Loan, Operating Costs To Operating Income, and Capital Adequacy Ratio Against Return On Asset in Conventional Commercial Banks In Indonesia In 2021-2024 - Subagyo, Adellia Monica Putri Valentine; Sukaris, Sukaris (INNOVATION RESEARCH JOURNAL, 2026)
This study aims to analyze the influence Non Performing Loan(NPL), Operating Costs to Operating Income (BOPO), and Capital Adequacy Ratio (CAR) against Return on Asset (ROA) in conventional commercial banks in Indonesia for the period 2021–2024. This study uses a quantitative approach with secondary data obtained from published banking financial reports and banking statistics published by the Financial Services Authority. Data collection was conducted through documentation, while the sampling technique used purposive sampling. Data analysis was conducted using multiple linear regression with the help of SPSS software and preceded by a classical assumption test. The partial test results indicate that NPL has no significant effect on ROA, BOPO has a significant effect on ROA, while CAR has no significant effect on ROA. Simultaneously, NPL, BOPO, and CAR have a significant effect on ROA. This finding indicates that operational efficiency is a dominant factor in determining bank profitability, while credit risk and capital adequacy have not shown a direct effect on profitability performance during the observation period. The limitations of this study lie in the number of variables used and the research time span. Therefore, further research is recommended to add other variables and expand the observation period to obtain more comprehensive results. Key words: Bank Profitability, BOPO, NPL, CAR.